OsWNK9 regulates the expression of key transcription factors, phytohormonal, and transporters genes to improve salinity stress tolerance in rice - Yogesh Negi; Kundan Kumar (Scientific Reports)
Abstract Rice is a staple food crop, and salinity stress severely hinders its growth and yield. Understanding the molecular mechanisms regulating salinity tolerance is essential and requires the identification and functional characterization of salt-tolerant genes to develop rice varieties with increased tolerance to salinity stress. With No Lysine Kinases (WNKs) are serine/threonine kinases involved in various abiotic stress responses. Earlier, we reported that overexpression of OsWNK9 mitigates salinity stress in Arabidopsis and rice. In the present study, we used transcriptomic analysis to provide molecular insights into the tolerance mechanism exhibited by the overexpression line of OsWNK9 (Oe-OsWNK9) under salinity stress. RNA-seq analysis revealed that the Oe-OsWNK9 exhibited significant enrichment of GO terms related to biological processes, including “response to abiotic stimulus,” “regulation of protein dephosphorylation,” “protein phosphorylation,” and “cell surface receptor signaling pathways”. The cellular component GO terms were also significantly enriched with “plasmodesma,” “plasma membrane,” “extracellular space,” “apoplast,” and “cell wall” terms. The molecular function component showed enrichment of genes associated with ADP, iron, and “polysaccharide binding,” “protein dimerization activity,” and “protein phosphatase 1 binding”. The KEGG pathway enrichment plot showed enrichment of metabolic pathways, phenylpropanoid biosynthesis, and biosynthesis of secondary metabolites. Also, we observed differential regulation of key genes involved in phytohormonal transport and metabolism, ionic homeostasis, and signal transduction pathways. This study provides new insights into the dynamics of key differential functional genes and the associated transcriptional regulatory networks involved in salt stress tolerance in rice.